Re-membering the Bard : David Greig’s and Liz Lochhead’sRe-visionary Reminiscences of “The Tempest” - Maria Elena Capitani (Parole Rubate, 2017)
The Tempest (1611) is one of those Shakespearean texts which have been adopted and adapted most frequently. This article explores two early Nineties appropriations of the Bard’s romance, that is David Greig’s unpublished monologue A Savage Reminiscence or (How to Snare the Nimble Marmoset), first performed in 1991, and Liz Lochhead’s The Magic Island, a rewriting of The Tempest for seven- to eleven-year-olds, first staged in 1993. Even if they differ from a variety of points of view, both Scottish Tempests retell the Shakespearean narrative through the lens of memory. In Greig’s appropriation, after being left alone on the island, a guilty Caliban recollects some past events – in particular his rape of Miranda – from his own marginalised perspective. Similarly, Lochhead’s The Magic Island, which adapts Shakespeare’s play to the needs and taste of a young audience by focusing on the theme of friendship, reconstructs the story retrospectively through the eyes of Prospero’s daughter. Through a web of intertextual references interwoven with contemporary echoes, Greig and Lochhead re-member and dismember their source problematizing any unimaginative subscription to the Shakespearean canon.